HISTOMORPHOLOGY OF THE OVARY OF RABBITS IN POSTNATAL ONTOGENESIS - Ibragimov Bakhodir Bakhtiyarovich (Science, education, innovation: modern tasks and prospects, 2025)
This article examines changes occurring in rabbit ovaries during postnatal development. The histomorphological structure of ovaries in rabbits of different ages was compared. The morphological structure of follicles and oocytes at different stages of development during oogenesis was determined under a microscope.